Biodiversity of fish in Penyerang River at District of Puding Besar, Bangka Regency - Andi Gustomi; Prihatin Ika Wahyuningrum; Eva Utami (Jurusan Akuakultur, Universitas Bangka Belitung, 2016)
Penyerang river is one of rivers which located in district of Puding Besar, Bangka regency. The mining and agricultural activities were increased at the district that lead to the decreasing of the quality of the environment, especially for the biodiversity of fish. The aim of this research was to investigate the diversity of fish, similarity index, and domination index of fish in Penyerang rivers, district of Puding Besar, Bangka Regency. The method used was survey-sampling method by placing six observation stationsin way of purposive sampling. It was divided on certain stations, such as up, middle and down stream station, whereas two for each stations.The data collected was chemical and physicalwater parameters and fish sampleby using gillnet, scoopnet and frock. The result shows that 18 fish species in Penyerang Rivers in District of PudingBesar , Bangka Regency composed of 13 genus and 9 families were found. The diversity of fish population and species in Penyerang River indicating on average range and was not dominate by certain species. Taken together, the populations of fish in Penyerang River were uniform.